2014
DOI: 10.1007/s00705-014-2055-x
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of bacteriophage therapy against Cronobacter sakazakii in Galleria mellonella (greater wax moth) larvae

Abstract: Cronobacter sakazakii, an opportunistic pathogen found in milk-based powdered infant formulae, has been linked to meningitis in infants, with high fatality rates. A set of phages from various environments were purified and tested in vitro against strains of C. sakazakii. Based on host range and lytic activity, the T4-like phage vB_CsaM_GAP161, which belongs to the family Myoviridae, was selected for evaluation of its efficacy against C. sakazakii. Galleria mellonella larvae were used as a whole-animal model fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(16 citation statements)
references
References 58 publications
0
15
1
Order By: Relevance
“…Work is ongoing to examine other MOIs. Although previous work reported the inoculation of bacteria/phages by intrahaemocoelic injection (Abbasifar et al, 2014; Beeton et al, 2015), we found ingestion via the oral route more efficient at inducing colonization and producing reproducible therapy results. The observed higher efficacy of the phages when used prophylactically rather than with remedial treatment is consistent with a previous report (Beeton et al, 2015).…”
Section: Discussioncontrasting
confidence: 73%
See 2 more Smart Citations
“…Work is ongoing to examine other MOIs. Although previous work reported the inoculation of bacteria/phages by intrahaemocoelic injection (Abbasifar et al, 2014; Beeton et al, 2015), we found ingestion via the oral route more efficient at inducing colonization and producing reproducible therapy results. The observed higher efficacy of the phages when used prophylactically rather than with remedial treatment is consistent with a previous report (Beeton et al, 2015).…”
Section: Discussioncontrasting
confidence: 73%
“…Although the insect is used as an infection model for various pathogens (Mukherjee et al, 2010; Ramarao et al, 2012; Hill et al, 2014; Beeton et al, 2015) and antimicrobial testing (Seed and Dennis, 2009; Abbasifar et al, 2014; Beeton et al, 2015; Olszak et al, 2015), to our knowledge this report is the first published data to describe its use to study C. difficile colonization and phage treatment. We established that 10 5 C. difficile cells were sufficient for colonization to occur in the larvae and to cause the first and total mortality at 24 and 60 h respectively post-infection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mammalian models are crucial for testing the efficacy of phages prior to human trials, but drawbacks include the need for sufficient infrastructure, substantial costs as well as the need for ethical approval. G. mellonella larvae have been used to examine numerous host-pathogen interactions ranging from studies of pathogenicity to antimicrobial activity, with a small number of these examining the potential for phage therapy [12][13][14].…”
Section: Discussionmentioning
confidence: 99%
“…Two studies in particular have characterized the ability of bacteriophages to reduce and control growth of C. sakazakii in PIF. 34,35 However, the application of bacteriophages is not limited to environmental control but can also be used in vivo, as has been demonstrated in insect and mouse infection models, where bacteriophages were shown to protect insect larvae 36 or reduce bacterial load in urinary tract infections in mice. 37 Bacteriophages have furthermore been successfully used as immuno-stimulants to increase expression of pro-inflammatory host factors.…”
Section: Antibiotic Resistance and Alternative Means Of Controlmentioning
confidence: 99%